Analisis Deskriptif Ketepatan Penggunaan Antihipertensi di Salah Satu Puskesmas di Kabupaten Boyolali - Arvita Sari; Rita Septiana; Risma Sakti Pambudi (Journal Clinical Pharmacy and Pharmaceutical Science, 2024)
The Silent Killer was a nickname for hypertension. Hypertension was a dangerous disease that can attack anyone even without any complaints. Providing appropriate therapy can guarantee the success of therapy for hypertensive patients. This study aims to determine the percentage of correct drugs, correct indications, correct doses and correct patients regarding the administration of antihypertensive drugs at one of the Community Health Centers in Boyolali for the period January-June 2021. This was a type of retrospective descriptive research, with 106 samples taken from medical record data. The results of the study showed that 69.81% of hypertensive patients were female, 30.19% of patients were aged ≥65 years, 90.57% had no comorbidities and 74.53% were diagnosed with grade 1 hypertension. The antihypertensives given to the patients were adequate. The criteria for correct indication were 100%, correct patient was 96.23%, correct drug was 81.13% and correct dose was 93.40%.